2020
DOI: 10.1093/nar/gkaa641
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of edited CYb and COIII mitochondrial mRNAs is achieved by distinct mechanisms in Trypanosoma brucei

Abstract: Trypanosoma brucei is a parasitic protozoan that undergoes a complex life cycle involving insect and mammalian hosts that present dramatically different nutritional environments. Mitochondrial metabolism and gene expression are highly regulated to accommodate these environmental changes, including regulation of mRNAs that require extensive uridine insertion/deletion (U-indel) editing for their maturation. Here, we use high throughput sequencing and a method for promoting life cycle changes in vitro to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 87 publications
0
22
0
Order By: Relevance
“…Mitochondrial metabolism and gene expression are highly regulated to deal with all those complicated environmental changes across the complete life cycle alternating between the mammalian host and insect vector, including regulation of mRNAs that require extensive uridine insertion/deletion (U-indel) editing for their maturation, as has been described in other closely related Trypanosomatids ( Smith et al., 2020 ). To our knowledge, it is the first time describing a large repertoire of complete T. cruzi minicircle sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial metabolism and gene expression are highly regulated to deal with all those complicated environmental changes across the complete life cycle alternating between the mammalian host and insect vector, including regulation of mRNAs that require extensive uridine insertion/deletion (U-indel) editing for their maturation, as has been described in other closely related Trypanosomatids ( Smith et al., 2020 ). To our knowledge, it is the first time describing a large repertoire of complete T. cruzi minicircle sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Minicircles are exclusive to Trypanosomatids and they are directly involved in U-insertion/deletion editing system as they encode guide RNAs (gRNAs) ( Simpson et al., 2003 ; Aphasizhev and Aphasizheva, 2014 ; Smith et al., 2020 ). Moreover, it is suggested that both molecule populations are heterogeneous in the cell, showing strain-specific variations ( Westenberger et al., 2006 ; Messenger et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The region 5’ of an editing stop site can either be pre-edited or a junction. Junctions are areas of mis-editing, in which the sequences match neither the pre-edited nor fully edited sequence, and they are found in a majority of our partially edited A6, COIII and RPS12 mRNAs ( Table 1 ) (Simpson et al 2016; Smith et al 2020). TREAT defines junctions as extending from the 3’ most ES that does not match the fully edited sequence to the 5’ most editing site that shows any editing modification.…”
Section: Resultsmentioning
confidence: 99%
“…TREAT v0.03 (Simpson et al 2017) was used in this study. All reads were aligned to the published pre-edited and fully edited A6 and COIII mRNA sequences (Smith et al 2020), with the modification of COIII mRNA as described above. The number of standard reads (sequences with no non-T mismatches) and non-standard reads (sequences with non-T mismatches) are listed in ( Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation